2021
DOI: 10.1007/s00125-021-05384-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of C-reactive protein gene confers resistance to obesity and insulin resistance in rats

Abstract: Aims/hypothesis Besides serving as a traditional inflammatory marker, C-reactive protein (CRP) is closely associated with the development of obesity, diabetes and cardiovascular diseases as a metabolic and inflammatory marker. We hypothesise that CRP protein directly participates in the regulation of energy and glucose metabolism rather than just being a surrogate marker, and that genetic deficiency of CRP will lead to resistance to obesity and insulin resistance. Methods Crp gene deletion was achieved by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…In addition, the effect of metabolism should be taken into consideration, since human CRP exacerbated OA development in high-fat diet-fed mice [36]. And in the study of Yang's group, who used the same batch of CRP knockout rats as ours, CRP was found to regulate energy balance and glucose homeostasis through leptin's central effect and hypothalamic signalling [29]. These studies indicated that elevated CRP level during in ammation should be the premise for exploring the effect of CRP on OA, which is in uenced by in ammation progression, genetic variation and metabolism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the effect of metabolism should be taken into consideration, since human CRP exacerbated OA development in high-fat diet-fed mice [36]. And in the study of Yang's group, who used the same batch of CRP knockout rats as ours, CRP was found to regulate energy balance and glucose homeostasis through leptin's central effect and hypothalamic signalling [29]. These studies indicated that elevated CRP level during in ammation should be the premise for exploring the effect of CRP on OA, which is in uenced by in ammation progression, genetic variation and metabolism.…”
Section: Discussionmentioning
confidence: 92%
“…Adult female Sprague Dawley (SD) rats aged 10-12 weeks and weighing 350-400 g were used as controls for CRP-/-rats of the same age and weight. The CRP-/-rats were provided by Professor Zhigang Yang from Chongqing Medical School [29]. DNA sequencing was performed by Sangon Biotech (Shanghai, China) to determine the knockout e ciency in CRP-/-rats.…”
Section: Animals and Induction Of Tmj In Ammationmentioning
confidence: 99%
“…In addition, the effect of metabolism should be taken into consideration, since human CRP exacerbated OA development in high-fat diet-fed mice [36]. In the study of Yang's group, who used the same batch of CRP knockout rats as ours, CRP was found to regulate energy balance and glucose homeostasis through leptin's central effect and hypothalamic signalling [29]. These studies indicated that elevated CRP level during in ammation should be the premise for exploring the effect of CRP on OA, which is in uenced by in ammation progression, genetic variation and metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Experiments on rats indicate that a Crp KO causes both a reduced weight gain on an HFD and smaller food intake. The latter is apparently induced by the recently discovered direct control of leptin signaling by CRP [79]. Carriage of the intron rs1130864 AA genotype and ACCC haplotype for rs1130864 (intron), rs1205 (3 UTR), rs2794521 (2KB upstream), and rs3093062 (2KB upstream) of the CRP gene is associated with a higher BMI in Mexicans [138].…”
Section: The Complement Systemmentioning
confidence: 98%
“…Higher obesity, increased macrophage infiltration, but with predominance of anti-inflammatory M2 macrophages [76] Ccl2 Protection against obesity [77] Ccr2 Partial protection against diet-induced obesity [78] Crp (Rattus norvegicus) Reduction in weight gain and food intake [79] C3 Reduction in weight gain, but no reduction in WAT inflammation [80] C3aR…”
Section: Spontaneous Weight Gainmentioning
confidence: 99%